Любовь в маленьком городе - Подъяпольская Татьяна (GELEOS Publishing House, 2010)
Экземпляры: СФ-7 (20110622) / Инвентарный номер: 39670z7 / Цена: 234.33 / Сис.шифр: 84(2) / Авт.знак: П 45 / ГРНТИ: 17.82.31 / ББК: 84(2=Рус)